MUSLIM MINORITAS DAN WACANA GENDER DI AUSTRALIA - Munjin Munjin (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
In the context of nation-state, a group of society who embrance Islam can be called as a minority, for they are little innumber. They sometimes meet some unintended problems like politically marginalized, difficult to integrate, backward education, economy,a place for praying, permitted food and so on. The problem usually come from prejudice feeling or negative thinking from in the majority.But, the condition does not happen in Australia, even women are free to choose their proffesion. Interestingly, women have a better destinythan men. There are actually, many factors that cause the minority, i.g.; refugees, guestworkers, exiled, migrant, convertion and ethnicreligion cleansing.